2017
DOI: 10.1111/hsc.12457
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and difficulties of French professional home caregivers in supporting older people with Alzheimer's disease or alcohol misuse

Abstract: In France, few studies have examined home care when it comes to ageing support and even fewer have considered alcohol misuse in this context. The studies also show that being old and having alcohol use disorders are two unfavourable conditions for receiving help, whereas for the Alzheimer's disease, there is a clear need for optimal care. In shows that the professional home caregivers are involved in looking after not only people with Alzheimer's disease but also those with alcohol misuse. However, despite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Indeed, among recent studies using a similar procedure (i.e. interviews) the percentage of classified UC ranged from 60% to 74% (Bucci & Vanheule, 2018 ; Denoual, Dargentas, Roudaut, Balez, & Sizun, 2016 ; Guzmán-Osorio, Chávez-Vallejo, Monzerrat Silvat, Parrello, & Ioro, 2017 ; Moscato & Varescon, 2018 ). We first underlined that patients do not seem to feel as actors of their own health.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, among recent studies using a similar procedure (i.e. interviews) the percentage of classified UC ranged from 60% to 74% (Bucci & Vanheule, 2018 ; Denoual, Dargentas, Roudaut, Balez, & Sizun, 2016 ; Guzmán-Osorio, Chávez-Vallejo, Monzerrat Silvat, Parrello, & Ioro, 2017 ; Moscato & Varescon, 2018 ). We first underlined that patients do not seem to feel as actors of their own health.…”
Section: Discussionmentioning
confidence: 99%
“…The size of our study population (n = 10) is small in comparison to other lexicometric studies that we identified as similar to ours and that included from 17 to 100 participants [15,31,[33][34][35][36][37][38]. This prevented us from testing statistical associations between semantic outputs and patients' characteristics.…”
Section: Study Limitationsmentioning
confidence: 97%